Supporting Individuals with Intellectual Disabilities & Mental Illness - Melrose, Sherri; Open Textbook Library (Open Textbook Library, 2015)
This multidisciplinary resource develops topics of interest to all those who care about and for individuals with co-occurring intellectual disabilities and mental illness. Each chapter presents current evidence informed practice knowledge. Each topic is also presented with audio enabled text boxes emphasizing 'Key Points for Caregivers.' For those who are interested in background knowledge, we provided the comprehensive literature base. And, for those interested mainly in 'what to do,' we provided text box summaries for reading and listening.
CHAPTER 1: SUPPORT WORK: THE FUNDAMENTALS -- Introduction -- Guiding Principles for Support Work -- Historical Struggles -- Competencies Expected of Support Workers -- Conclusion -- References -- CHAPTER 2: WHAT'S IN A NAME? -- Introduction -- The Purpose of Naming -- Historical Perspective -- Guidelines for Choosing the Right Name -- Intellectual Disability -- What Is Intellectual Disability? -- The Impact of Names Beyond the Hurt Feelings: Implications for Service and Support -- Conclusion -- References -- CHAPTER 3: AN OVERVIEW OF MENTAL ILLNESS -- Introduction -- Background of Mental Health Care -- Indicators Associated with Disorders of Thinking -- Indicators Associated with Disorders of Mood -- Indicators Associated with Disorders of Behaviour -- Conclusion -- References -- CHAPTER 4: COMMON PHYSICAL CONCERNS -- Introduction -- Health Status -- Factors Affecting Health Status -- Common Health Challenges -- Impact of Support Providers on Health Status -- Health Promotion -- Conclusion -- References -- CHAPTER 5: WHEN THE PROBLEM IS PAIN -- Introduction -- Ethical Principles for Addressing Physical Health Conditions and Assessing Pain -- The Hierarchy of Pain Assessment Techniques -- Guiding Principles Pain Assessment -- Behavioural Pain Assessment Tools -- Picture Resources for Identifying Emotions of Physical Distress -- Pain and Health Care for Dually Diagnosed Persons -- Conclusion -- References -- CHAPTER 6: BEHAVIOUR THAT HURTS -- Introduction -- Overview of Applied Behavioural Analysis -- Strategies to Help Decrease Self-Injurious and Aggressive Behaviour -- Conclusion -- References -- CHAPTER 7: SEXUALITY -- Introduction -- Discussion Topics for Sexual Education Support -- Understanding Boundaries -- Providing Resources -- Differentiating between Challenging Behaviours and Sex Offending Behaviours -- Conclusion -- References --
In English.
Description based on print resource
Keywords: Social sciences -- Textbooks; Medicine -- Textbooks